Determination of the Optimum Point of Sampling, for the Evaluation of the Concentrations of Total Suspended Particles (TSP) in a Semiurban Colombian Area - Rojano, Roberto; Pérez, Jhonny; Galindo, Andrés; Mendoza, Yoma; Soto, Dairo; Toncel, Enrique (Revista Técnica da Faculdade de Engenharia da de Zulia)
To establish a monitoring network generates costs either in economic resource or in the human one. In this research a logical procedure was applied to facilitate the selection of the single site for the atmospheric monitoring of total suspended particles ”“TSP”“ whose sample volume is representative of the characteristics of the air present in the city of Sincelejo, Colombia. For the localization of the appropriate point of sampling, an inventory of the sources of emission of particles was carried out, obtaining a total of 34sources as a result with diverse contribution grades. Based on this information and on the emission factors developed by the EPA, the different emission rates were determined, which were used together with the prevalent meteorological conditions and the nomograme of Turner [1]. They allowed to establish the maximum concentrations of exposition to the poluent and the distances from the corresponding source. The best individual localization for the evaluation of the levels of PST was the Chamber of Commerce Building of the city. The sampling pilot of one month, every other day, gave concentrations of particles between 26,52 and 76,01 Î¼g/m3, with a geometric average of 45,07 Î¼g/m3, value below (55%) of that settled down by the Colombian norm, ordinance 02 of 1982 (<100 Î¼g/m3).